Hejmen armchair / Nazeem Shahiry Mohd Ayub - Mohd Ayub, Nazeem Shahiry (Universiti Teknologi MARA, Kedah, 2024)
The Hejmen armchair, inspired by the majestic humpback whale, embodies the elegance and grace of these magnificent marine creatures. Designed to offer both comfort and aesthetic appeal, this armchair integrates oceanic elements into a functional piece of furniture. The backrest, shaped to mimic the graceful curve of a whale's fluke, provides ergonomic support, while the deep ocean blue cushions evoke the serenity of the sea. The armrests, seat, and backrest are all upholstered in high-quality fabric and padded, ensuring a cohesive and comfortable experience. The choice of soft, durable fabric enhances the overall tactile experience and adds warmth to the design. The chair's slightly curved legs mimic the humpback whale's sleek appearance and provide stability. The Hejmen Armchair, with its refined design and sea life-inspired tranquility, is the perfect balance of art and utility